Biomass partitioning in a future dry and CO2 enriched climate: Shading aggravates drought effects in Scots pine but not European black pine seedlings. Issue 4 (17th January 2019) - Bachofen, Christoph; Wohlgemuth, Thomas; Moser, Barbara
Abstract: Climate change alters both water and CO2 availability for plants, but it is largely unknown how they interact with light to affect tree seedling establishment and early growth. Light availability is often regulated by forest management, thus understanding how these resources co‐limit the regeneration success of tree species and populations with contrasting drought tolerances is essential for adaptive forest management and particularly for assisted migration. We studied biomass partitioning of 3‐year‐old Scots pine ( Pinus sylvestris ) and European black pine ( Pinus nigra ) seedlings in response to combined effects of light (22% and 40% shade), soil water availability (moist and dry conditions) and CO2 (ambient and elevated), and examined the responses of seedlings from Central Alpine and Mediterranean origin. Seedlings of nine populations with varying drought tolerances were grown in a common garden in the European Central Alps. Shoot height, vertical root length, shoot and root biomass of the plants were assessed at the end of the third growing season. Under 40% shade and dry conditions, P. sylvestris seedlings severely reduced shoot biomass, resulting in an increased specific shoot height (SSH) compared to seedlings under 22% shade and moist conditions. In contrast, P. nigra seedlings retained a constant shoot biomass under all treatment combinations. Seedlings from drier origin were generally larger, heavier and had longer vertical roots than those from wetter locations. In order to keep up shoot height, seedlings from wetter origins disproportionately increased SSH under shaded conditions compared to populations from drier origin. Synthesis and applications . Under high light availability, Scots pine ( Pinus sylvestris ) and European black pine ( Pinus nigra ) seedlings were well adapted to dry conditions. Moderate shading, however, substantially reduced Scots pine but not black pine growth, and potentially amplified the vulnerability of Scots pine seedlings to drought. Optimising light conditions in forests, for example by thinning, may thus enhance early Scots pine regeneration in a drier future climate. Abstract : Under high light availability, Scots pine ( Pinus sylvestris ) and European black pine ( Pinus nigra ) seedlings were well adapted to dry conditions. Moderate shading, however, substantially reduced Scots pine but not black pine growth, and potentially amplified the vulnerability of Scots pine seedlings to drought. Optimising light conditions in forests, for example by thinning, may thus enhance early Scots pine regeneration in a drier future climate.